Modification of TOGAF 9.2 Enterprise Architecture Framework to Meet the Needs of Startup Companies - Azzahra, Haniya
A startup company is an organization that is dedicated to creating innovations in the form of new solutions to solve a problem under conditions of high uncertainty. Startup Genome states that 70% of the 3200 startup companies fail because of premature scaling. Premature scaling occurred when the startup company entered the rapid scaling stage. At this stage it is necessary to apply enterprise architecture as a formal and structured strategic planning to manage the increasing complexity of the system and avoid premature scaling. However, there are obstacles in the application of enterprise architecture to startup companies due to the characteristics of startup companies, namely having a broad target market, rapid growth, products or services offered based on technology and nonexistent, having high uncertainty, dynamic change, having resources limited, and very dependent on founder effect. Nevertheless, the application of Enterprise Architecture to startup companies can be done by adjusting the enterprise architecture framework with the characteristics of startup companies. The Open Group Architecture Framework (TOGAF) is one of the frameworks that can be used to develop Enterprise Architecture at startup companies. The TOGAF framework provides a tailoring design method, namely modifying the existing TOGAF framework so that it can produce a TOGAF framework that meets the needs of startup companies, which is the main objective of this final project. To achieve this goal, various activities were carried out including analyzing startup company characteristics, analyzing framework selection, TOGAF ADM 9.2 mapping with startup company reference models, analyzing adjustments to the TOGAF ADM stages, and describing the design modifications framework consisting of stages, phases, and steps that are equipped with input, output, and the process of each step and connectedness between steps. In the end, a modified TOGAF ADM enterprise architecture framework on TOGAF 9.2 to meet the needs of startup companies is resulted.